Multimodal MRI study of the relationship between plaque characteristics and hypoperfusion in patients with transient ischemic attack - Sui, Ying; Sun, Jiali; Chen, Yue; Wang, Wei (Frontiers in Neurology, 2023)
Objective: Transient ischemic attack is a significant risk factor for acute cerebral infarction.Previous studies have demonstrated that hypoperfusion in patients with transient ischemic attack was associated with the recurrence of transient ischemic attack, stroke, and persistent worsening of neurological symptoms. Moreover, transient ischemic attack patients classified as high-risk group according to the ABCD 2 score have a higher incidence of stroke. Therefore, the objective of this study was to investigate the plaque characteristics of transient ischemic attack patients with concomitant cerebral hypoperfusion using multimodal MRI, as well as hemodynamic changes in the high-risk group with transient ischemic attack patients.A total of 151 patients with transient ischemic attack were prospectively recruited for this study. All enrolled patients underwent multimodal MRI, including DWI, TOF-MRA, HR-VWI, and DSC-PWI. Finally, 56 patients met the inclusion criteria. Based on DSC-PWI images, patients were divided into two groups: hypoperfusion (n=41) and non-hypoperfusion (n=15). Clinical baseline characteristics and plaque characteristics were analyzed between the two groups. Furthermore, within the hypoperfusion group, patients were further classified into low-risk (n=11) and high-risk (n=30) subgroups based on the ABCD 2 score. Hemodynamic differences between these subgroups were also analyzed.Compared with the non-hypoperfusion group, the hypoperfusion group had a significantly higher prevalence of hypertension (68.3% vs. 33.3%, P=0.019) and hyperhomocysteinemia (65.9% vs. 33.3%, P=0.029). Moreover, the hypoperfusion group exhibited more significant luminal stenosis degree [41.79±31.36 vs. 17.62±13.62, P=0.006] and greater NWI (57.1%±20.47% vs. 40.21%±21.56%, P=0.009) compared to the non-hypoperfusion group. In addition, the high-risk group dentified by the ABCD 2 score had a higher rMTT [117.6(109.31-128.14) vs. 108.36(100.67-119.92), P=0.037].Transient ischemic attack patients with hypoperfusion exhibited a higher prevalence of hypertension and hyperhomocysteinemia, as well as higher luminal stenosis degree, and greater NWI. Furthermore, Transient ischemic attack patients in the high-risk group demonstrated higher MTT.